2008
DOI: 10.1111/j.1365-294x.2007.03621.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonization history of the Swiss Rhine basin by the bullhead (Cottus gobio): inference under a Bayesian spatially explicit framework

Abstract: The present distribution of freshwater fish in the Alpine region has been strongly affected by colonization events occurring after the last glacial maximum (LGM), some 20,000 years ago. We use here a spatially explicit simulation framework to model and better understand their colonization dynamics in the Swiss Rhine basin. This approach is applied to the European bullhead (Cottus gobio), which is an ideal model organism to study fish past demographic processes since it has not been managed by humans. The molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 66 publications
2
104
0
1
Order By: Relevance
“…ABC techniques in demo-genetics studies (see, e.g., Tallmon et al 2004;Excoffier et al 2005a;Hamilton et al 2005;Chan et al 2006;Hickerson et al 2006;Shriner et al 2006;Pascual et al 2007;Legras et al 2007;Rosenblum et al 2007;Cornuet et al 2008;Neuenschwander et al 2008). Indeed, setting up simulation files for an arbitrarily complex model can be done in a few hours using existing simulation programs (e.g., Hudson 2002;Laval and Excoffier 2004;Cornuet et al 2008), allowing one to focus on realistic evolutionary models rather than restricting oneself only to models for which specific programs have been developed.…”
Section: Resultsmentioning
confidence: 99%
“…ABC techniques in demo-genetics studies (see, e.g., Tallmon et al 2004;Excoffier et al 2005a;Hamilton et al 2005;Chan et al 2006;Hickerson et al 2006;Shriner et al 2006;Pascual et al 2007;Legras et al 2007;Rosenblum et al 2007;Cornuet et al 2008;Neuenschwander et al 2008). Indeed, setting up simulation files for an arbitrarily complex model can be done in a few hours using existing simulation programs (e.g., Hudson 2002;Laval and Excoffier 2004;Cornuet et al 2008), allowing one to focus on realistic evolutionary models rather than restricting oneself only to models for which specific programs have been developed.…”
Section: Resultsmentioning
confidence: 99%
“…This ABC technique has been applied essentially to relatively complex scenarios of colonization (Pascual et al 2007), spatial expansion (Estoup et al 2004;François et al 2008;Hamilton et al 2005a;Neuenschwander et al 2008), pest introduction (Miller et al 2005), pathogen transmission (Tanaka et al 2006), population bottleneck (Chan et al 2006), complex phylogeography (Hickerson et al 2006), and admixture ).…”
Section: Approximate Bayesian Computationmentioning
confidence: 99%
“…They assume that individuals can only disperse through stream corridors and no longer through a two-dimensional landscape (e.g., BAR-RIER: Manni et al 2004;STREAM TREES: Kalinowski et al 2008). Another example is the extension of the spatially explicit coalescent simulation program SPLATCHE to linear habitats (AQUASPLATCHE: Neuenschwander 2006), which was used to study the colonisation history of the Swiss Rhine basin by bullhead (Cottus gobio) (Neuenschwander et al 2008b). Other riverscape genetics studies investigated the influence of the spatial structure of river networks on population connectivity (e.g., Labonne et al 2008;Morrissey & de Kerckhove 2009), and identified barriers to gene flow for fish (see Storfer et al 2010).…”
Section: Individual-based Simulation Modelsmentioning
confidence: 99%